2017
DOI: 10.1111/jcpe.12781
|View full text |Cite
|
Sign up to set email alerts
|

The innate host response in caries and periodontitis

Abstract: Far less investigated than adaptive immunity, innate immune responses are an emerging scientific and therapeutic frontier. Soluble mediators of the innate response provide a network of signals to organize the near immediate molecular and cellular response to infection, including direct and immediate antimicrobial activity. Further studies in human disease and animal models are generally needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 148 publications
4
82
0
2
Order By: Relevance
“…The breakthrough of monoclonal antibodies has serious participation in the discovery of some specific subclasses of T-cells: cytotoxic, helper, suppressor, killer etc. The mechanisms and pathways of the immune response are very complex, with a lot of different cytokines and other inflammatory mediators being involved in the development of apical and periodontal pathological conditions 7,8,9,10 . Our examination of the level of immunoglobulins in the three examined groups has shown certain changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakthrough of monoclonal antibodies has serious participation in the discovery of some specific subclasses of T-cells: cytotoxic, helper, suppressor, killer etc. The mechanisms and pathways of the immune response are very complex, with a lot of different cytokines and other inflammatory mediators being involved in the development of apical and periodontal pathological conditions 7,8,9,10 . Our examination of the level of immunoglobulins in the three examined groups has shown certain changes.…”
Section: Discussionmentioning
confidence: 99%
“…Meyle et al summarized that the innate immunity is primary responsible for the rapid molecular and cellular response of the host in the inflammatory processes 9 . These…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Such cells own the ability migrate to the infection site as a result of the increased release of chemokines and cytokines. 30 Periodontal bacteria trigger the host immune response which causes release of inflammatory mediators and cytokines in the periodontal tissues causing periodontal breakdown. 31 It has been demonstrated that a large network of cytokines plays a critical role in the pathogenesis of periodontitis leading to soft tissue destruction and bone resorption.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Although dental caries pathogenesis originates on the non-shedding, hard surface of the tooth, the immunology of the human host nevertheless plays a critical role in disease prevention or progression. Both the innate and adaptive arms of the immune system influence caries, and past proof-of-principle studies explored the possibility of several active and passive vaccine strategies to prevent caries (reviewed in (24, 25)). In recent years, however, research regarding the immunological component of dental caries has lagged well behind study of the microbiological component.…”
Section: Introductionmentioning
confidence: 99%